Bibliometric study on research trends in artificial intelligence and mathematics education - Daulay, Leni Agustina; Nasution, Awal Kurnia Putra; Asnawi, Asnawi; Zahari, Cut Latifah; Wardani, Hizmi (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2025)
This research analyzes the emerging AI and Mathematics Education nexus from the years 2015 to 2024, aiming to ascertain primary research patterns, significant contributors, and thematic progressions in the specialized bibliometric discourse. By conducting a bibliometric analysis of 840 articles indexed in Scopus, this research uncovers accelerated growth, especially post-2020, in scholarly interest concerning AI applications in mathematics education. The findings emphasize a notable decline in using teaching methods grounded in pedagogy to more sophisticated techniques focused on leveraging machine learning and tutoring systems to maximize educational achievement for students. The United States and China are pointed out as the main players in the mapped research framework. Unlike other studies that vaguely address AI and education, this review stands out in providing a comprehensive assessment of how AI tools are integrated within the teaching of mathematics and tracking the evolution of research in this context. The design seeks to aid educators, policymakers, and even researchers focusing on the intersection of technological advancements and educational reform in mathematics teaching.